The Jurisprudence Of The Sokoto State Administration Of Criminal Justice Law 2019: Innovative Provisions, Redlines And Suggestions For Future Reforms - Abdullahi , Ibrahim (Advances in Social Sciences Research Journal, 2020)
This article appraises the jurisprudence, innovative provisions, redlines inherent in the Sokoto State Administration of Criminal Justice Law 2019 and make suggestions for future reforms. Sokoto State is one of States in Nigeria that has domesticated the Administration of Criminal Justice Act 2015 (ACJA 2015) through the signing into law of the Sokoto State Administration of Criminal Justice Law, 2019 by his Excellency, the Executive Governor of Sokoto State, Rt. Hon. Aminu Waziri Tambuwal (Mutawallen Sokoto) to take care of the problems of incessant delay in the criminal justice system. This article uses the doctrinal research methodology in gathering information’s and observes the need to look holistically at the issue of poor draftsmanship while provisions that runs counter to the Constitution should be addressed. The article recommended amongst others that the provisions relating to expeditious legal advice from the office of the Attorney General of Sokoto State and prohibition against lay prosecutions cannot be effective if the manpower at the Ministry of Justice is not improved upon and the welfare of the lawyers at the said Ministry is not taken care of. Barring the above, it is a new dawn for Sokoto State in the administration of Criminal Justice.